Hypertension and Cognitive Health Among Older Adults in India - Farron, Madeline R. (J Am Geriatr Soc, 2020)
OBJECTIVES: To assess the prevalence of diagnosed and undiagnosed hypertension and their relationship to cognitive function in older adults in India. DESIGN: Longitudinal Aging Study in India–Diagnostic Assessment of Dementia (LASI-DAD), an in-depth national study of late-life cognition and dementia. SETTING: Geriatric hospitals and respondents’ homes across 14 states in India. PARTICIPANTS: N = 2,874 individuals aged 60 years and older from LASI-DAD. MEASUREMENTS: Hypertension was identified by self-report of physician diagnosis or measured blood pressure (BP) of 140/90 mmHg or higher. Undiagnosed hypertension was defined as hypertensive BP measurements, but no physician diagnosis. Controlled hypertension was defined as BP lower than 140/90 mmHg among those with a physician diagnosis. Total hypertension included both diagnosed and undiagnosed hypertension. A summary cognition score, derived from the sum of 18 cognitive tests administered in the LASI-DAD (range = 0–360) was used to assess cognitive function. RESULTS: Total hypertension prevalence was 63.2% (41.5% diagnosed and 21.6% undiagnosed). Among those with hypertension, 34.5% were undiagnosed, 34.2% were diagnosed but uncontrolled, and 31.3% were diagnosed and controlled. Neither diagnosed nor undiagnosed hypertension was related to cognitive function in fully adjusted models. Older age, female sex, less education, being widowed, rural residence, residing in the north or central regions, being in a scheduled caste or tribe, low consumption, being underweight, and history of stroke were all independently associated with worse cognitive test performance. CONCLUSION: Two-thirds of older Indian adults had hypertension, with the majority being undiagnosed or diagnosed but not adequately controlled. Hypertension was not independently associated with cognitive function, whereas sociodemographic factors were independently related to cognitive function.